A biofeedback‐guided programme or pelvic floor muscle electric stimulation can improve early recovery of urinary continence after radical prostatectomy: A meta‐analysis and systematic review. Issue 10 (4th May 2021) - Sciarra, Alessandro; Viscuso, Pietro; Arditi, Alessandro; Mariotti, Gianna; De Berardinis, Ettore; Di Pierro, Giovanni Battista; Canale, Vittorio; Gentilucci, Alessandro; Maria Busetto, Gian; Maggi, Martina; Eisenberg, Michael L.; Vilson, Fernandino; et al.
Abstract: Purpose: Urinary incontinence (UI) after radical prostatectomy (RP) is an early side effect after catheter removal. This systematic review and meta‐analysis were conducted to compare different forms of non‐invasive treatments for post‐RP UI and to analyse whether the addition of biofeedback (BF) and/or pelvic floor muscle electric stimulation (PFES) to PF muscle exercise (PFME) alone can improve results in terms of continence recovery rate. Materials and Methods: A literature search was performed following the PRISMA guidelines. We performed a cumulative meta‐analysis to explore the trend in the effect sizes across subgroups during a 12‐months follow‐up. Results: Twenty‐six articles were selected. At baseline after RP and catheter removal, mean pad weight varied extremely. At 1‐ and 3‐months intervals, mean difference in pad weight recovery from baseline was significantly higher using guided programs (BF, PFES or both) than using PFME alone (3‐months: PFME 111.09 g (95%CI 77.59‐144.59), BF 213.81 g (95%CI −80.51‐508‐13), PFES 306.88 g (95%CI 158.11‐455.66), BF + PFES 266.31 g (95%CI 22.69‐302.93); P < .01), while at 6‐ and 12‐months differences were similar ( P > .04). At 1‐ and 3‐months intervals, event rate (ER) of continence recovery was significantly higher using guided programs than using PFME alone (3‐months: PFME 0.40 (95%CI 0.30‐0.49), BF 0.49 (95%CI 0.31‐0.67), PFES 0.57 (95%CI 0.46‐0.69), BF + PFES 0.75 (95%CI 0.60‐0.91); P < .01), while at 6‐ and 12‐months ERs were similar. Conclusions: Regarding non‐invasive treatment of UI secondary to RP, the addition of guided programs using BF or/and PFES demonstrated to improve continence recovery rate, particularly in the first 3‐month interval, when compared with the use of PFME alone.